Application of E-SCM in the Automotive Industry - Erlangga Hakim Manurung; Musdiansyah Putra (Penerbit Jurnal Indonesia, 2022)
Technological developments have shaped internet-based markets around the world. This internet- based market has supported many industries, one of which is the automotive industry. The automotive industry is an important component in the country's economic growth. This paper focuses on electronic supply chain management or e-SCM in the automotive industry and the impact of implementing e-SCM on organizations. The method used by the author is a literature review method where the author searches and studies journals, both national and international on the internet. The results of several journals found that ease of use and perceived usefulness influence the adoption of e-SCM systems in organizations. It was concluded that, perceived usefulness and ease of application of e-SCM technology can improve performance in the automotive industry.